2023
DOI: 10.1002/gj.4674
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on near‐field edge wave run‐ups generated by landslides in narrow reservoirs

Abstract: Edge waves generated by subaerial landslide‐tsunamis (SLTs) often have potentially huge amplitudes that can endanger human lives, offshore structures, coastal cities and port facilities around reservoirs. Maximum edge wave run‐up (RuM) is the most important parameter for SLT hazard mitigation in an engineering context. This study aimed to investigate the effects of the hill slope angle α on RuM, the first edge wave run‐up Ru1 and the first edge wave decay in the near field Ru1(r/h) through 84 laboratory experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…To mitigate SLT hazards in an engineering context, maximum edge wave run‐up (RuM) is a critical parameter. Liu, Wang, Xiao, et al (2023) aims to investigate the impact of hill slope angle α on RuM, first edge wave run‐up Ru1, and first edge wave decay in the near field Ru1(r/h) through 84 laboratory experiments conducted in a three‐dimensional river channel with α values ranging from 15° to 40°. The study found that for smaller α values, RuM increased with the increase in α , while for larger α values exceeding 30°, RuM decreased with the increase in α .…”
Section: Research Outputs Of This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate SLT hazards in an engineering context, maximum edge wave run‐up (RuM) is a critical parameter. Liu, Wang, Xiao, et al (2023) aims to investigate the impact of hill slope angle α on RuM, first edge wave run‐up Ru1, and first edge wave decay in the near field Ru1(r/h) through 84 laboratory experiments conducted in a three‐dimensional river channel with α values ranging from 15° to 40°. The study found that for smaller α values, RuM increased with the increase in α , while for larger α values exceeding 30°, RuM decreased with the increase in α .…”
Section: Research Outputs Of This Special Issuementioning
confidence: 99%
“…To mitigate SLT hazards in an engineering context, maximum edge wave run-up (RuM) is a critical parameter. Liu, Wang, Xiao, et al (2023) In addition, the study also discussed the first edge wave run-up decay along the shore. These findings have important implications for the preliminary hazard assessment of SLTs.…”
Section: Research Outputs Of This Special Issuementioning
confidence: 99%